2009
DOI: 10.1007/s11367-009-0085-5
|View full text |Cite
|
Sign up to set email alerts
|

Application of life cycle assessment to the production of man-made crystal glass

Abstract: Background, aim and scope This paper presents a life cycle assessment (LCA) of the manufacturing process of crystal glass products in order to evaluate the potential environmental impacts due to a crystalware company located in Colle di Val d'Elsa, Siena (Italy). Since there is not any published research specifically focussed on crystal production to our knowledge, outcomes from this study would represent a first documented evidence gathered from an LCA of crystal glass products. Once a detailed description of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
5
1
Order By: Relevance
“…This really makes us wonder whether the values provided by the normalization could be biased in some way, probably because the marine aquatic ecotoxicity is too high or the remaining impact categories are too low. These conclusions are contrasted with several investigations, whose authors came up with results that shared similar trends [23,[33][34][35], so it would not be an error in the LCA calculations. The research conducted by Heijungs et al [36] is noteworthy, in which they describe the phenomenon and its reasons.…”
Section: Standardized Analysis Of Aggregates Without Residue and Lighcontrasting
confidence: 91%
“…This really makes us wonder whether the values provided by the normalization could be biased in some way, probably because the marine aquatic ecotoxicity is too high or the remaining impact categories are too low. These conclusions are contrasted with several investigations, whose authors came up with results that shared similar trends [23,[33][34][35], so it would not be an error in the LCA calculations. The research conducted by Heijungs et al [36] is noteworthy, in which they describe the phenomenon and its reasons.…”
Section: Standardized Analysis Of Aggregates Without Residue and Lighcontrasting
confidence: 91%
“…Table 5 shows similar impact reduction results to those discussed in the previous section, except for an unusual result in the category of ecotoxicity of the marine environment, an unexpected value given that aggregate production does not represent a directly toxic activity for the marine environment. After an exhaustive search for the reasons, Heijungs et al [58] concluded that this generalized phenomenon should not be considered an error in the study, but a bias in the category calculation system, as is the case in some similar studies [50,[59][60][61].…”
Section: Standardized Analysis Of Traditional and Residue-added Light...mentioning
confidence: 99%
“…The glass containers then undergo a surface treatment to improve mechanical strength: it is necessary to proceed with annealing which consists of a heating up to 550 C and a slow cooling to room temperature (Pulselli et al, 2009).…”
Section: Manufacturing Systemmentioning
confidence: 99%